Implementation of Learning during the Covid-19 Pandemic: A Case Study of Sjarifudin Kendal Islamic Elementary School - Farhani, Nuriana (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
This study aims to identify information regarding the application of learning during the Covid-19 pandemic at Sjarifudin Islamic Elementary School and to analyze whether learning at Sjarifudin Islamic Elementary School during the pandemic can be implemented properly and effectively. The benefit of this research is to find out how learning was implemented during the Covid-19 pandemic at Sjarifudin Islamic Elementary School and whether learning at Sjarifudin Islamic Elementary School during the Covid-19 pandemic was effective. This research is a case study research using a qualitative descriptive approach. A qualitative approach is used to describe the application of learning during the Covid-19 pandemic at Sjarifudin Islamic Elementary School. Based on the results of the research above, it can be concluded that learning at Sjarifudin Islamic Elementary School during the Covid-19 pandemic was carried out in a blended learning manner, namely through the WhatsApp group and coming to students' homes. The learning process can be said to be successful even though online learning only uses the WhatsApp application and offline learning is carried out at students' homes in rotation.